Heritage language socialization in Chinese American immigrant families: prospective links to children's heritage language proficiency. Issue 8 (14th September 2021) - Chen, Stephen H.; Zhou, Qing; Uchikoshi, Yuuko
ABSTRACT: Though a number of language socialization processes are theorized to promote children's heritage language proficiency (HLP), little research has considered these processes in a single study and examined their prospective relations to multiple domains of HLP in school-age children. In a two-wave longitudinal study of Chinese American children of immigrant parents ( N  = 258, age = 7–11 years), language socialization processes (e.g. adult HL use at home, parental attitudes towards HL, child participation in HL classes or extracurricular activities) were assessed using parent reports and behavioral observation at Time 1 (1st to 2nd grade). Children's HLP (Cantonese or Mandarin) was assessed using vocabulary and literacy tests at Time 2. Results of structural equation modeling showed that adults' Chinese language use with children at home predicted children's higher Chinese receptive and expressive vocabulary two years later, and children's participation in Chinese language extra-curricular activities predicted their higher Chinese receptive and expressive vocabulary and higher Chinese word reading. By contrast, parental valuing of Chinese language and children's exposure to Chinese media did not predict children's Chinese proficiency. These findings provided support for the benefits of HL use at home and HL classes in promoting HL development in children in immigrant families.